Translation of the Mahābhārata and Cognitive Linguistics - Jurewicz, Joanna (Folia Orientalia, 2026)
This article analyses the battle descriptions in the Mahābhārata from the perspective of cognitive linguistics, focusing on how the epic’s oral character shapes its linguistic and narrative structure. Drawing on the author’s experience as a translator of Sanskrit into Polish, the study explores the relationship between word order and viewpoint construal, showing how syntactic strategies guide the listener’s imagination and evoke emotional responses. Using a passage from Book VI, the analysis demonstrates how shifts in prominence and perspective—expressed through zooming in and out—create a dynamic interplay between proximity and distance, slowing down or accelerating narrative time. These changes enable the audience to experience the battle both as spectacle and as tragedy. The article argues that the Mahābhārata’s orality fosters an imagery-oriented mode of storytelling, in which grammar itself becomes a tool of visualisation. A comparison with Alex Cherniak’s English translation highlights how the constraints of English syntax can obscure these cognitive effects, raising broader questions about the limits of translation when it comes to rendering construal and viewpoint.